1982
DOI: 10.4269/ajtmh.1982.31.163
|View full text |Cite
|
Sign up to set email alerts
|

Quartan Malaria Following Splenectomy 36 Years after Infection *

Abstract: Quartan malaria developed following splenectomy 36 years after infection in a 63-year-old hypertensive man. The patient underwent nephrectomy because of left renal calculus, increasing proteinuria and hypertension. Splenectomy was done additionally because metastasis of renal tumor to the spleen was suspected at the operation. Attention is drawn to the long silent infection with Plasmodium malariae and to the importance of the spleen in malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…This observation also has implications for human malaria. It is known that in patients with a previous history of malaria, often with no new infections for many years, following splenectomy suffer an abrupt onset of Pladmodium falciparum (26), P. malariae (27), and Plasmodium vivax (28) malarias. These splenectomies usually follow splenic trauma.…”
Section: Discussionmentioning
confidence: 99%
“…This observation also has implications for human malaria. It is known that in patients with a previous history of malaria, often with no new infections for many years, following splenectomy suffer an abrupt onset of Pladmodium falciparum (26), P. malariae (27), and Plasmodium vivax (28) malarias. These splenectomies usually follow splenic trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Human infection by P. malariae is often asymptomatic and long-lasting (up to last 40 years in the absence of re-infection) with blood stages probably persisting for a lifetime [26–29]. Patient evaluation has been reported due to recrudescence induced by splenectomy performed for malaria-unrelated reasons [30] or when malaria is acquired from transfusions with Plasmodium -infected blood, as observed in Latin America [31]. …”
Section: Malaria-causing Parasitesmentioning
confidence: 99%
“…Only a small number of African, Asian, and American cases have been described in the official literature. [2][3][4][5][6][7][8][9][10][11][12][13] On the basis of four Thai case reports, Looareesuwan and others concluded that the spleen may not be essential for the processes leading to parasite clearance in partially immune patients. 10 The rare clinical and parasitologic features of Plasmodium falciparum infections that we report in two immune, splenectomized men living in French Guiana do not support this conclusion.…”
Section: Introductionmentioning
confidence: 99%